2019
DOI: 10.1038/s41598-019-39996-4
|View full text |Cite
|
Sign up to set email alerts
|

Pitx2 cholinergic interneurons are the source of C bouton synapses on brainstem motor neurons

Abstract: Cholinergic neuromodulation has been described throughout the brain and has been implicated in various functions including attention, food intake and response to stress. Cholinergic modulation is also thought to be important for regulating motor systems, as revealed by studies of large cholinergic synapses on spinal motor neurons, called C boutons, which seem to control motor neuron excitability in a task-dependent manner. C boutons on spinal motor neurons stem from spinal interneurons that express the transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Only briefly expressed in the somites, FOXF1 marks other mesoderm derived tissues, including the splanchnic mesoderm or the sclerotome [ 57 ]. The other TFs, PAX2 [ 58 ], PRDM12 [ 59 ], TFAP2β [ 60 ] are found in neurons of the peripheral and/or central nervous system, so are EYA2 [ 61 ], LMO4 [ 62 ] and PITX2 [ 63 ]. This suggests that FP-RMS cells are not simply undifferentiated muscle cells, but rather as cells with their own transcriptional status.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only briefly expressed in the somites, FOXF1 marks other mesoderm derived tissues, including the splanchnic mesoderm or the sclerotome [ 57 ]. The other TFs, PAX2 [ 58 ], PRDM12 [ 59 ], TFAP2β [ 60 ] are found in neurons of the peripheral and/or central nervous system, so are EYA2 [ 61 ], LMO4 [ 62 ] and PITX2 [ 63 ]. This suggests that FP-RMS cells are not simply undifferentiated muscle cells, but rather as cells with their own transcriptional status.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of PAX3-FOXO1 bound CRMs in the vicinity of 40% of these FP-RMS associated genes and of PAX DNA motifs within at least half of these CMRs represents a means by which PAX3/7 dependent developmental gene networks are co-opted by PAX-FOXO1 expressing cells [11,12,70]. In addition, the presence of TFs known to also strongly influence the differentiation of PAX dependent embryonic lineages [51,[53][54][55][56][57]59,62,63,71] might also contribute to the FP-RMS dysfunctional transcriptional state [1,12,72].…”
Section: New Markers Of Fp-rms and Their Regulation By The Pax-foxo1smentioning
confidence: 99%
“…For instance, the execution of a motor command is tightly controlled via class I interneurons (Ia-IN and Ib-IN, inhibitory: glycinergic), Renshaw cells (inhibitory: glycinergic/GABAergic), and class II interneurons (II-IN, excitatory: glutamatergic/cholinergic) (Côté et al, 2018; Figure 2). While class II-IN are the sole source of cholinergic inputs (Rozani et al, 2019), they are not the only neuromodulatory input LMN receive (Heckman et al, 2003). Descending tracts primarily from brainstem nuclei modulate LMN excitability via noradrenergic (from locus coeruleus) and rich serotonergic (from raphe nucleus) inputs, mainly facilitating their excitation (Heckman et al, 2003;Bruinstroop et al, 2012; Figure 2).…”
Section: Spinal Circuit Elements Contributing To Lmn Degenerationmentioning
confidence: 99%
“…The best characterized cholinergic interneurons, also called partition cells, reside near the central canal and express Pitx2. Elegant studies have demonstrated they are the source of cholinergic C boutons that synapse either ipsi-or contralaterally onto motor neuron cell bodies and modulate their excitability 2,3,[44][45][46] . In our dataset, we found 8 interneuron clusters with different transcriptomic profiles and specific markers (Fig.…”
Section: Cholinergic Interneuronsmentioning
confidence: 99%